Numerical Study Of Turbulent Thermal-Hydraulic Performance Of Al2o3-Water Nanofluid In Channel With Triangular Baffles - Abed Ahmed a, Mohammed (Anbar Journal of Engineering Sciences, 2016)
In this paper, turbulent forced convection of nanofluid flow in channel with isoscelestriangularbaffles is numerically investigated over Reynolds number ranges of 5000-10000.One baffle mounted on the bottom wall of channel and another mounted on the top wall.Al2O3-water nanofluid with nanoparticles volume fraction of 4% and nanoparticles diametersof 25 nm is used. The governing continuity, momentum and energy equations as well as thelow Reynolds number k-ε model of Launder and Sharma have been solved using finitevolume method. The effect of baffle height, baffle distance as well as Reynolds number onthe flow and thermal characteristics have been presented and discussed. It is found that theenhancement ratio of the average Nusselt number as well as the fraction factor increase withincreasing in the baffles height. It is also found that the enhancement ratio of the averageNusselt number increases as the distance of top baffle decrease. Furthermore, the bestthermal-hydraulic performance of channel with triangular baffles using nanofluid can beobtained at baffle height of 2.5 mm, distance of the top baffle of 40 mm and Reynoldsnumber of 5000.